2019
DOI: 10.17152/gefad.421615
|View full text |Cite
|
Sign up to set email alerts
|

Matematik Öğretiminde Dijital Oyun Tasarlamanın Öğretmen Adaylarının Yaratıcılıklarına Etkisi

Abstract: Bu araştırmanın amacı, eğitsel dijital oyun tasarlamanın öğretmen adaylarının yaratıcılıklarına etkisini araştırmaktır. Araştırma, ön test-son test kontrol gruplu yarı deneysel araştırma deseninde tasarlanmıştır. Çalışma grubunu, Türkiye'de bir devlet üniversitesinin eğitim fakültesinde öğrenim görmekte olan ve matematik öğretimi dersini alan sınıf öğretmenliği öğrencileri oluşturmaktadır. 14 gönüllü öğrenci deney grubu ve 11 öğrenci de kontrol grubu olarak belirlenmiştir. Araştırmanın deney grubunda, 14 hafta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
(21 reference statements)
1
3
0
2
Order By: Relevance
“…For this result, it was seen that the students developed a positive attitude towards the science course. When the relevant literature is examined, it is seen that there are studies showing similar results to the results of this study (Akça & Topsakal, 2020;Aksoy, 2014;Aygün, 2019;Can, 2010;Can, 2017;Çelik, 2017;Çetin, 2016;Demir, 2012;Eltem, 2018;Gürbüz, 2019;Gürpınar, 2017;Korkmaz, 2018;Liu & Chen, 2013;Özkan & Şentürk, 2020;Şahin, 2016;Tok, 2016;Tokgöz, 2017;Tortop, 2007;Torun, 2011;Turanlı, 2012;Yeşilkaya, 2013). Özkan, Akça & Topsakal (2020), seventh grade "Cells and Divisions" unit in the study carried out within the scope of the seventh grade "Cells and Divisions" unit, where the students developed a positive attitude towards the science course after the application, Aksoy (2014), the students within the scope of the sixth grade mathematics course had a meaningful effect by increasing their attitude scores, Can (2010), eighth grade "Structure of Substance and Features" unit.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…For this result, it was seen that the students developed a positive attitude towards the science course. When the relevant literature is examined, it is seen that there are studies showing similar results to the results of this study (Akça & Topsakal, 2020;Aksoy, 2014;Aygün, 2019;Can, 2010;Can, 2017;Çelik, 2017;Çetin, 2016;Demir, 2012;Eltem, 2018;Gürbüz, 2019;Gürpınar, 2017;Korkmaz, 2018;Liu & Chen, 2013;Özkan & Şentürk, 2020;Şahin, 2016;Tok, 2016;Tokgöz, 2017;Tortop, 2007;Torun, 2011;Turanlı, 2012;Yeşilkaya, 2013). Özkan, Akça & Topsakal (2020), seventh grade "Cells and Divisions" unit in the study carried out within the scope of the seventh grade "Cells and Divisions" unit, where the students developed a positive attitude towards the science course after the application, Aksoy (2014), the students within the scope of the sixth grade mathematics course had a meaningful effect by increasing their attitude scores, Can (2010), eighth grade "Structure of Substance and Features" unit.…”
Section: Discussionsupporting
confidence: 67%
“…In other words, it was determined that GBL had no effect on students' level of self-efficacy in the science course. There are studies in the literature that support this result (Aksoy, 2014;Bayırtepe & Tüzün, 2007). Aksoy (2014) concluded that there was no meaningful effect between both groups in his study within the scope of the sixth grade mathematics course, and that the games did not have an impact on the students' perceptions of self-efficacy within the scope of Bayırtepe & Tüzün (2007), seventh grade computer course.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Considering the importance of these skills in daily life, it has been observed that individuals who are more successful in coping with difficulties and reaching their goals are individuals with high-level thinking skills (Yüksel, 2015). According to Aksoy and Küçük-Demir (2019), the use of digital media in mathematics education is one of the important features that increase the level of creative thinking. It is seen that different and creative thinking, which has been mentioned recently, has great importance in investigating reasoning approaches in mathematics education in many respects (National Council of Teachers of Mathematics [NCTM], 1989).…”
Section: Introductionmentioning
confidence: 99%